Distinct neural correlates of emotional and cognitive empathy in older adults. Issue 1 (30th April 2015) - Moore, Raeanne C.; Dev, Sheena I.; Jeste, Dilip V.; Dziobek, Isabel; Eyler, Lisa T.
Abstract: Empathy is thought to be a mechanism underlying prosocial behavior across the lifespan, yet little is known about how levels of empathy relate to individual differences in brain functioning among older adults. In this exploratory study, we examined the neural correlates of affective and cognitive empathy in older adults. Thirty older adults ( M =79 years) underwent fMRI scanning and neuropsychological testing and completed a test of affective and cognitive empathy. Brain response during processing of cognitive and emotional stimuli was measured by fMRI in a priori and task-related regions and was correlated with levels of empathy. Older adults with higher levels of affective empathy showed more deactivation in the amygdala and insula during a working memory task, whereas those with higher cognitive empathy showed greater insula activation during a response inhibition task. Our preliminary findings suggest that brain systems linked to emotional and social processing respond differently among older adults with more or less affective and cognitive empathy. That these relationships can be seen both during affective and non-emotional tasks of "cold" cognitive abilities suggests that empathy may impact social behavior through both emotional and cognitive mechanisms. Highlights: We examined neural correlates of affective and cognitive empathy in older adults. Participants completed cognitive and emotional fMRI tasks. Affective empathy was related to greater deactivation of the amygdala and insula. Cognitive empathy was related to greater activation of the insula. Empathy may impact social behavior through both emotional and cognitive mechanisms.